Wandering souls : journeys with the dead and the living in Viet Nam - Karlin, Wayne (New York : Nation Books, 2009)
On March 19, 1969, First Lieutenant Homer R. Steedly, Jr., shot and killed a North Vietnamese soldier, Hoang Ngoc Dam, when they met on a jungle trail. Steedly took a diary--filled with beautiful line drawings--from the body of the dead soldier, which he subsequently sent to his mother for safekeeping. Thirty-five years later, Steedly rediscovers the forgotten dairy and begins to confront his suppressed memories of the war that defined his life, deciding to return to Viet Nam and meet the family of the man he killed to seek their forgiveness. Fellow veteran and award-winning author Wayne Karlin accompanied Steedly on his remarkable journey. In Wandering Souls he recounts Homer's movement towards a recovery that could only come about through a confrontation with the ghosts of his past--and the need of Dam's family to bring their child's "wandering soul" to his own peace. Wandering Souls limns the terrible price of war on soldiers and their loved ones, and reveals that we heal not by forgetting war's hard lessons, but by remembering its costs.
Includes bibliographical references and index.
Keywords: Steedly, Homer, -- 1946-; Hoang, Ngoc Dam, -- d. 1969.; Vietnam War, 1961-1975 -- Psychological aspects; Vietnam War, 1961-1975 -- Casualties; Vietnam War, 1961-1975 -- Veterans -- United States; Veterans -- Mental health -- United States; Bereavement -- Religious aspects -- Buddhism